2012
DOI: 10.1007/978-1-4614-4118-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Highly Multiplexed Proteomic Platform for Biomarker Discovery, Diagnostics, and Therapeutics

Abstract: Progression from health to disease is accompanied by complex changes in protein expression in both the circulation and affected tissues. Large-scale comparative interrogation of the human proteome can offer insights into disease biology as well as lead to the discovery of new biomarkers for diagnostics, new targets for therapeutics, and can identify patients most likely to benefit from treatment. Although genomic studies provide an increasingly sharper understanding of basic biological and pathobiological proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…We also reported that this analysis was confounded by large scale differences between the study sites. This observation motivated a series of studies investigating the effect of sample handling on biomarker discovery [22,23]. The result of these studies was the development of a set of SMVs which allowed us to quantify the magnitude of confounding pre-analytical variation introduced by sample collection differences.For example, the cytoplasmic molecular chaperone HSP90 is a well established lung cancer marker and therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…We also reported that this analysis was confounded by large scale differences between the study sites. This observation motivated a series of studies investigating the effect of sample handling on biomarker discovery [22,23]. The result of these studies was the development of a set of SMVs which allowed us to quantify the magnitude of confounding pre-analytical variation introduced by sample collection differences.For example, the cytoplasmic molecular chaperone HSP90 is a well established lung cancer marker and therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…Such chemically modified aptamers are particularly well-suited to selection schemes that favor long-lived complexes; hence, we refer to this class of aptamers as SOMAmers (slow off-rate modified aptamers). SOMAmers have transformed the landscape of proteomics, leading to a sensitive and highly multiplexed platform with applications in biomarker discovery and early-stage disease detection (De Groote et al, 2013;Gold et al, 2010Gold et al, , 2012Loffredo et al, 2013;Lollo et al, 2014;Mehan et al, 2012Mehan et al, , 2013Ostroff et al, 2010Ostroff et al, , 2012, as well as sandwich-based single analyte detection assays (Ochsner et al, , 2014, rapid histochemistry tools (Gupta et al, 2011), and therapeutic applications (Gelinas et al, 2014;Gupta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SELEX has been successfully applied to a variety of targets including proteins [44], small peptides [45], metal ions [46], and small organic molecules [47]. In basic medical research, this method has been used for drug screening [48][49][50][51], clinical diagnosis [52], and treatment [53]. Whether the library is enriched or not is one of the important indicators of SELEX selection success or failure.…”
Section: Discussionmentioning
confidence: 99%